2008
DOI: 10.1007/s11627-007-9101-2
|View full text |Cite
|
Sign up to set email alerts
|

Protocorm-like body (PLB) formation and plant regeneration from the callus culture of Dendrobium candidum Wall ex Lindl.

Abstract: An efficient system was established for a higher frequency of protocorm-like body (PLB) formation from the callus of Dendrobium candidum Wall ex Lindl. The calluses were induced from longitudinally bisected segments of protocorms and subcultured two times every 40d on Murashige and Skoog medium with macronutrients at half strength, micronutrients at full strength, 2% sucrose, and with 8.8μM 6-Benzylaminopurine. PLB formation was achieved when calluses were transferred onto the same basal medium without any pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 33 publications
10
45
0
7
Order By: Relevance
“…These globules gradually grew in size, having no vascular connections with the surrounding peripheral tissues and eventually transformed into PLBs. The PLBs proliferated further to produce secondary PLBs as reported earlier (Zhao et al 2008).…”
Section: Resultssupporting
confidence: 61%
“…These globules gradually grew in size, having no vascular connections with the surrounding peripheral tissues and eventually transformed into PLBs. The PLBs proliferated further to produce secondary PLBs as reported earlier (Zhao et al 2008).…”
Section: Resultssupporting
confidence: 61%
“…Zhao et al (2008) reported that the majority of Dendrobium candidum PLBs produced secondary PLBs originated from cells of the interior or exterior of the embryogenic callus. Chen and Chang (2006) also observed continuous production of somatic embryos in Phalaenopsis amabilis through secondary embryogenesis directly from leaf explants.…”
Section: Discussion Plbs Inductionmentioning
confidence: 99%
“…Many authors states that PLBs are somatic embryos (Hossain et al, 2013;Lee et al, 2013), or that somatic embryogenesis is the initial step on the PLBs formation (Zhao, Wu, Feng, & Wang 2008). Through histological and histochemical studies, Lee et al (2013) demonstrated that during the early stages of PLB formation, the cells show cytological characteristics and cell wall markers similar to zygotic embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…con 0,2 mg/l -1 de ANA y en Cymbidium sp. con 0,1 mg/l -1 de ANA (Ávila-Díaz et al, 2009;Zhao et al, 2008).…”
Section: Diferenciación Y Enraizamiento De Protocormosunclassified
“…Debido a esta facilidad, los protocormos se han utilizado como explantes en trabajos de embriogénesis somáti-ca y organogénesis directa e indirecta, cuyas técnicas son aplicadas ampliamente en la micropropagación vegetativa (Tuong et al, 2004;Zhao et al, 2008).…”
Section: Introductionunclassified